PENGARUH KUALITAS PELAYANAN, CITRA DESTINASI DAN KEARIFAN LOKAL TERHADAP MINAT BERKUNJUNG KEMBALI KE SABA BADUY DENGAN ELECTRONIC WORD OF MOUTH SEBAGAI VARIABEL INTERVENING - Soelton, Dr. Mochamad (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2024)
Baduy people are very careful about their customs and protect their natural surroundings. Because they realize that they live with nature and coexist with nature. The original Baduy tribe consists of the Inner Baduy and the Outer Baduy. The Baduy tribe still maintains traditions, customs and anti-modernization in terms of clothing, lifestyle and others. The purpose of this study was to examine the effect of Service Quality, Destination Image, and Local Wisdom on Intentions to Visit Saba Baduy Culture with Electronic Word Of Mouth as an intervening variable. This research was conducted using primary data, namely by distributing online questionnaires via google form and disseminated through social media namely Instagram, Line and Whatsapp. The sampling technique used is purposive sampling. Data processing using Partial Least Square (Smart-PLS) version 3.2.9. The results showed that the variables of Service Quality, Destination Image and Local Wisdom partially had a positive and significant effect on Electronic Word of Mouth. While the variables of Service Quality, Destination Image and Electronic Word of Mouth partially each have a positive and significant effect on Revisit Intention, while local wisdom has no significant effect on Revisit Interest. Electronic Word of Mouth is able to mediate Destination Image on interest in revisiting.